2022
DOI: 10.1126/science.abg9868
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing treatment-induced emergence of antibiotic resistance in bacterial infections

Abstract: Treatment of bacterial infections currently focuses on choosing an antibiotic that matches a pathogen’s susceptibility, with less attention paid to the risk that even susceptibility-matched treatments can fail as a result of resistance emerging in response to treatment. Combining whole-genome sequencing of 1113 pre- and posttreatment bacterial isolates with machine-learning analysis of 140,349 urinary tract infections and 7365 wound infections, we found that treatment-induced emergence of resistance could be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(91 citation statements)
references
References 37 publications
4
78
1
Order By: Relevance
“…The second issue is the importance of considering the preexisting genetic diversity in bacterial communities when assessing the potential for AMR evolution. Our results from patient JWC, together with findings from other recent studies 24,29,30 , show that genetic diversity fuels AMR evolution. Most research to date on within- patient evolution of AMR (including this study) has failed properly to screen for community diversity.…”
Section: Discussionsupporting
confidence: 86%
“…The second issue is the importance of considering the preexisting genetic diversity in bacterial communities when assessing the potential for AMR evolution. Our results from patient JWC, together with findings from other recent studies 24,29,30 , show that genetic diversity fuels AMR evolution. Most research to date on within- patient evolution of AMR (including this study) has failed properly to screen for community diversity.…”
Section: Discussionsupporting
confidence: 86%
“…Emergence of antimicrobial resistance in patients can also be predicted based on their past treatment history, clinical risk factors, and past colonization by resistant isolates. 112 Future work may rely further upon predictions of patient risks for resistant infections using metagenomics of the human microbiome. Taken together, the use of new methodology can aid in developing more nuanced models of the resistome, moving the field from descriptors of the presence of ARGs toward an improved understanding of the risks and clinical relevance of ARG abundance and transmission in the human microbiome.…”
Section: Next-generation Approaches To Detect and Predict Arg Transmi...mentioning
confidence: 99%
“…The literatures reported that the re‐establishment of those bacterial defense systems required a long‐term evolution brought by clinically dedicated AbR genes. [ 53,54 ] In contrast, our MWH treatment on MDR E. coli bacteria only lasted for 10 min. Therefore, we speculated that the genetic evolution of MDR E. coli bacteria would unlikely develop any new AbR in such short period of time.…”
Section: Discussionmentioning
confidence: 99%